Dynamic model for evaluation of medical devices maintenance in developing countries - Ali Mohammed Nasser Abdo; Amr Abdelrahman Sharawy; Manal Abdelwahed (Cairo : Ali Mohammed Nasser Abdo, 2015)
In spite of the existence of several behavioral analysis tools for maintenance systems, managers in most hospitals of developing countries till find difficulties to define maintenance strategies able to significantly improve the overall performance of medical devices. Proper maintenance policies can reduce overall medical devices operation cost, decrease degradation and increase availability. This thesis presents a system dynamics simulation model that was designed to evaluate the initiative contributions of preventive maintenance and corrective maintenance towards improving the overall performance of medical devices in developing countries in terms of operational availability, degradation, total cost of maintenance, and maintenance cost effectiveness. The model was built based on the response from the maintenance managements in the hospitals of developing countries to a simple questionnaire which was prepared to collect actual values for model variables. The study proposes and formulates better maintenance policies to achieve higher operational availability and lower degradation
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Syatems and Biomedical Engineering
Issued also as CD
Keywords: Maintenance policies; Medical devices; Statistical analysis